Extraction of oil from Mahkota Dewa seed with nutraceutical properties by using subcritical and supercritical CO2 - Muhammad Munzir bin Halib
The nutraceutical and pharmaceutical values of vegetable oil play very important roles in human health as everybody is consuming vegetable oil in their diet. Plant products or by-products had become the source of interest in pharmaceutical industry as they were rich of bioactive compounds. Phaleria macrocarpa, also known as Mahkota dewa is one of the family of Thymelaceae. This plant was used to treat acne, allergies, blood diseases, cancer, diabetes mellitus, high blood pressure, impotency, liver and heart diseases, kidney disorders, migraine, rheumatism, stroke, various skin diseases and so on. The aims of the present study were to extract fats and oils from Mahkota dewa seed using soxhlet extraction (SE), CO2 soxhlet and supercritical CO2 (scCO2). The yields using SE, CO2 soxhlet and scCO2 were approximately 60.83 ± 0.7%, 31.26 ± 5.3% and 54.23 ± 0.0%, respectively. The physicochemical and biochemical properties of the MDO were shown that the MDO contains high amounts of unsaturated fatty acids and low amounts of saturated fatty acid. However, the CO2 soxhlet extract has irregularity amounts of unsaturated and saturated fatty acids due to the low extraction temperature and pressure used in the study. The physicochemical property (slip melting point) found lowest in the SE extract (-9.15 ± 0.01 oC) and followed by the scCO2 extract (1.86 ± 0.14 oC) and CO2 soxhlet extract (25.49 ± 0.01 oC). Overall, the scCO2 extract represents a promising method to produce a nutraceutical vegetable based oil. Moreover, the study also aimed to analyse antioxidant of the MDO. such as total phenolic contents (TPC), 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay. The TPC was observed highest in the CO2 soxhlet extract (0.7297 ± 0.008 mg GAE/g) and followed by scCO2 extract (0.404 ± 0.005 mg GAE/g) and soxhlet extract (0.1824 ± 0.0006 mg GAE/g) at concentration of 4 mg/mL. The DPPH radical scavenging activity and antioxidant reducing power were found highest in the CO2 soxhlet extract with 24.9701 ± 1.1446 % and 0.7122 ± 0.0026 nm, respectively. The identification of the fatty acids constituents from the MDO was carried out using gas chromatography-mass spectrometry and the characterization of the MDO physico-chemical properties were analysed using established and standard methods. The palmitic acid (15.25%), oleic acid (41.75%), linoleic acid (34.19%) and stearic acid (6.10%) were found as major fatty acids in MDO of scCO2 extract. Finally, a lethal concentration (LC50) of the MDO against the zebrafish embryo toxicity (ZET) was analysed. The present study was able to clarify the toxicity of the MDO against the zebrafish embryos. The LC50 of MDO found in the SE, CO2 soxhlet and scCO2 extracts were 0.5 mg/mL, 2.33 mg/mL and 1.33 mg/mL, respectively. The MDO could be converted to vegetable oil with high value of nutraceutical properties and high amount of polyunsaturated fatty acids within it. The possible commercialization is to withdraw non-local vegetable oil from Malaysia market and instead with a cheaper vegetable oil of Mahkota dewa seed oil.